BATASAN ETIKA GURU DALAM INTERAKSI DENGAN PESERTA DIDIK DI RUANG DIGITAL - Muhammad Irfani Falah; Lutfiyah; Qodiron; Khasanah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology has transformed the pattern of interaction between teachers and students from being limited to the classroom to becoming broader through various digital platforms. This transformation facilitates communication and supports the learning process; however, it also presents challenges related to ethical boundaries and professionalism within pedagogical relationships. This study aims to analyze the ethical boundaries of teacher–student interactions in digital spaces and to identify the principles of professionalism that should be implemented to maintain the quality of educational relationships. The study employed a qualitative approach using a library research method. Data were collected from various literature sources, including books, scientific journals, research findings, and documents relevant to digital ethics, teacher professionalism, and technology-based educational interactions. Data analysis was conducted using a descriptive qualitative method through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that digital interactions have the potential to blur the boundaries between personal and professional spaces, which may lead to ethical dilemmas, privacy violations, and a decline in teachers’ professional authority if not managed appropriately. Teachers need to uphold professional principles through the use of respectful language, appropriate communication timing, the selection of suitable platforms, and the separation of personal and professional accounts. Furthermore, strengthening digital literacy, implementing professional codes of ethics, and developing digital interaction guidelines are essential steps in fostering healthy, safe, and educational communication between teachers and students in the digital era.